Respuesta :

Answer: (2,0) and (1,-3)

Step-by-step explanation:

The solutions of the equations will be (-2, 0) and (1, -3).

What is the solution to the equation?

The distribution of weights to the variables involved that establishes the equilibrium in the calculation is referred to as a result.

The equations are given below.

y = x² - 4        ...1

y = - x - 2       ...2

From equations 1 and 2, then we have

x² - 4 = - x - 2

x² + x - 2 = 0

Factorize the equation, then we have

x² + 2x - x - 2 = 0

x(x + 2) - 1(x + 2) = 0

(x + 2)(x - 1) = 0

x = -2, 1

At x = -2, the value of y will be

y = - (-2) - 2

y = 0

At x = 1, the value of y will be

y = - 1 - 2

y = -3

Then the solutions of the equations will be (-2, 0) and (1, -3).

The graph is given below.

More about the solution of the equation link is given below.

https://brainly.com/question/545403

#SPJ2

Ver imagen jainveenamrata